Male germline stem cells developmental and regenerative potential - Orwig, Kyle E.; Brian P. (Stem Cell Biology and Regenerative Medicine, 2011)
Scientists investigating germ cells have, over the past 15 years, originated discoveries and innovations that give us valuable insights into the mechanisms that regulate not just stem cell function, but human development in its widest sense. With contributions from some of the leading researchers in the field, Male Germline Stem Cells: Developmental and Regenerative Potential assesses the implications of these discoveries for understanding the fundamental biology of germline stem cells as well as their potential for human stem cell-based therapies. This monograph covers many of the fundamental issues now being explored by today?s generation of stem cell researchers, including the field's potential for regenerative medicine. Ranging from an assessment of the pluripotency of primordial germ cells and their possible applications in treating testicular cancer, to the recovery of once-mordant fertilization-competent sperm, this volume has it all. It is a reference point for any scientist involved in related research as well as being a timely summation of what could prove to be a hugely exciting and very fruitful area of inquiry.